Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/diagnostics12010082
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Model for Predicting Unscheduled 72 h Return Visits to the Emergency Department by Patients with Abdominal Pain

Abstract: Seventy-two-hour unscheduled return visits (URVs) by emergency department patients are a key clinical index for evaluating the quality of care in emergency departments (EDs). This study aimed to develop a machine learning model to predict 72 h URVs for ED patients with abdominal pain. Electronic health records data were collected from the Chang Gung Research Database (CGRD) for 25,151 ED visits by patients with abdominal pain and a total of 617 features were used for analysis. We used supervised machine learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Also, our report demonstrated that ML would be a better approach to provide a prediction model than multivariate logistic regression, which mainly focuses on the association between dependent and independent variables. The AUROC in this study was almost the same as that in previous studies that used ML technique, approximately 0.74–0.83 with a different algorithm 13–15. However, in some studies with multivariate logistic regression, the concordance (C)-statistic, which is often used to assess the ability of a risk factor to predict outcome, ranged from 0.55 to 0.74 4.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Also, our report demonstrated that ML would be a better approach to provide a prediction model than multivariate logistic regression, which mainly focuses on the association between dependent and independent variables. The AUROC in this study was almost the same as that in previous studies that used ML technique, approximately 0.74–0.83 with a different algorithm 13–15. However, in some studies with multivariate logistic regression, the concordance (C)-statistic, which is often used to assess the ability of a risk factor to predict outcome, ranged from 0.55 to 0.74 4.…”
Section: Discussionsupporting
confidence: 76%
“…Hong et al indicated that gradient-boosting models that leveraged clinical data were superior to traditional logistic regression models built on administrative data to predict ED revisit 14. Hsu et al developed an ML model, the voting classifier model, to predict ED revisit in patients with abdominal pain 15. These works shed light on the use of a prediction model for ED revisit based on an ML algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 72-hour unscheduled ED revisit rate is considered a healthcare quality indicator, as unscheduled ED revisits are associated with ED crowding, higher healthcare expenditure, and poorer medical experiences (28-30). Previous studies have also revealed that mental illness is a risk factor for unscheduled ED revisits and have attributed this to unclear discharge instructions, ine cient discharge systems, and inadequate post-ED follow-ups (31)(32)(33). To address this issue, various strategies such as multidisciplinary approaches, integrated discharge systems, and post-ED care programs have been found to be effective in reducing unscheduled ED revisits (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we attempted to predict 72-hour URVs in ED patients with abdominal pain using the ML model. [22] A crucial yet unfulfilled objective is to validate this model using future data. In this study, we not only refined our data to adjust our previous prediction model but also evaluated the model performance in future data validation during the COVID-19 era.…”
Section: Introductionmentioning
confidence: 99%